Assessing suicidality in adult ADHD patients: prevalence and related factors - Gabriele Di Salvo; Camilla Perotti; Lorenzo Filippo; Camilla Garrone; Gianluca Rosso; Giuseppe Maina (Annals of General Psychiatry)
Abstract Background The association between Attention-deficit hyperactivity disorder (ADHD) and suicidality has been subject of growing interest for research in the latest years. Suicidality was generally assessed categorically and without the use of validated instruments, leading to heterogeneous or even conflicting evidence. The prevalence of both suicidal ideation and attempts varies considerably, and the associated risk factors remain unclear. Our study investigated suicidality in ADHD using a dimensional approach and a validated and internationally recognized instrument. Our primary aim was to evaluate the prevalence of suicidal ideation (SI), severe suicidal ideation (SSI), suicidal behavior (SB) and non suicidal self-injury behavior (NSSIB) in a sample of adult patients with ADHD. The second objective was to identify sociodemographic and clinical features associated with increased risk of suicidality in these patients. Methods The sample included 74 adult patients with clinical diagnosis of ADHD. Suicidality was assessed by administering the Columbia-Suicide Severity Rating Scale. Logistic regressions were used to examine predictors of SI, SSI, SB and NSSIB. Results The lifetime prevalence of SI and SSI were 59.5% and 16.2%, respectively. The 9.5% of patients showed lifetime SB, while NSSIB was found in 10.8% of the subjects. Lifetime SI was associated with severity of inattentive symptoms during adulthood, low self-esteem and impairment in social functioning. Lifetime SSI appeared related to severity of inattentive symptoms during childhood, attentional impulsiveness and number of hospitalizations, while physical activity appeared to be protective. The prevalence of lifetime SB and NSSIB did not appear significantly related to any socio-demographic or clinical feature. Conclusions Adults with ADHD should be considered at risk of suicide and it is important to determine which patients are at higher risk, in order to guide preventive interventions. The association between ADHD and suicidal ideation did not appear to be influenced by psychiatric comorbidities, but rather by inattention itself, which represents the core symptom of ADHD.